Fuzzy terminal sliding mode control for extracting maximum marine current energy. (October 2015) - Gu, Ya-jing; Yin, Xiu-xing; Liu, Hong-wei; Li, Wei; Lin, Yong-gang
Abstract: A new fuzzy terminal sliding mode control strategy is proposed to extract the maximum marine current energy. The control strategy mainly consists of a fuzzy logic controller for deriving the reference q -axis generator current and a non-singular terminal sliding mode current controller capable of accurately tracking the derived reference generator current. A swell filter is also involved in the control strategy to improve the generator power quality in case of swell effects. The detailed design process and stability condition analysis of this control strategy have been thoroughly investigated. The effectiveness of the proposed control strategy has been evaluated in a 60 kW marine current power system. Comparative results demonstrate that the proposed control strategy can be employed to more effectively capture the maximum marine current power and to considerably eliminate the generator power ﬂuctuations as compared with a conventional second-order sliding mode control method. Highlights: Using a new control strategy to harvest the maximum energy from marine currents. Designing the strategy based on the fuzzy logic and a non-singular terminal sliding mode controller. Using the fuzzy logic to derive the maximum power points. Using the sliding mode controller to track the maximum power points. The proposed strategy can effectively and accurately extract the maximum power.